Modified palm oil fuel ash (pofa) as quartz replacement for the production of porcelain - Durumin Iya, Sani Garba (2019)
Utilization of silica rich ash such as palm oil fuel ash (POFA) in the ceramic industry due to the increasing demand for porcelain with improved performance is inevitable. Wastes are produced from the industry in form of empty fruits bunches, kernel and fibers. Palm oil industries burned the waste to produce heat to the boiler and generate electricity, the ash produced is known as palm oil fuel ash. POFA has similar chemical property with quartz, thus can be used as quartz replacement. The objectives of this research are to modify POFA, determined its effect on physico-mechanical properties of porcelain and develop a formulation model. To remove the moisture of POFA, the powder was dried in an oven at 110 °C for 24 hours and ground to a sufficient fineness ≤ 50 μm for 12 hours at 250 rev/min. POFA powder underwent heat and HCL acid treatments. Standard porcelain of 50 % clay, 25 % feldspar and 25 % quartz was adopted. Quartz was substituted with POFA at 0, 15, 20 and 25 wt.% and mixed homogeneously with the composition of porcelain, dry pressed into pallets at 91 MPa and sintered at 1100 °C, 1150 °C, 1200 °C and 1250 °C for 2 hours soaking time. Modified POFA (SiO2, Al2O3, Fe2O3, MgO, CaO, and P2O5) were then added to the optimum composition (1150 °C, 15 wt.% of POFA and 2 molar HCl acid treatment) at 1, 2, 3, 4, 5, 10 and 15 wt. % mixed homogeneously, dry pressed and sintered at 1150 °C to identify their effect on physico-mechanical properties of porcelain. Densification was achieved at lower sintering temperature by addition of POFA. Due to formation of mullite and crystalline phase, the highest values of bulk density, compressive strength, and Vickers micro hardness were found to increase by addition of Fe2O3 at 5 wt. % as 2.515 g/cm3, 177.08 MPa and 829 HV respectively. The results of developed polynomial regression models show a very good prediction similar to the experimental value. Hence, POFA has a greater future in ceramic industry due to its flexibility and chemical properties. It is therefore evidently concluded that, addition of Fe2O3 at 5 wt. % enhanced both physical and mechanical properties of porcelain.